MODERN VIEW TO PITYRIASIS VERSICOLOR: SOME ASPECTS OF PATHOGENESIS AND CLINICAL FEATURES IN CONDITIONS OF TORRID CLIMATE - M.A. ABDULLOEVA; P.T. ZOIROV (Avicenna Tajik State Medical University, 2017)
Objective: Identify perspiration, skin pH, and clinical features in patients with pityriasis versicolor in conditions of torrid climate. Methods: In the period of 2008-2011 years, there were 110 patients examined with the diagnoses of pityriasis versicolor (Pityrosporum) in the local clinical hospital No. 1, in Dushanbe.They were 63.6% men (70 persons), and 36.4% - of them women (40 persons), which part of them were rural residents 53.6%, and others were urban residents - 46.4%. The highest number of cases of diseases has mentioned with people in the age of 17 to 35 years (80.9%). Control group comprised to 30 healthy persons. The diagnosis of pityriasis versicolor was determined based on positive Besnier's symptoms, Balzer tests, yellowish-brown fluorescence at Wood's light, as well as revealing of a typical microscopic picture of "spaghetti and meatballs". Colorimetric method was used to determine the skin pH. For quality assessment of perspiration intensity in patients with pityriasis versicolor was used perspiration indicator IIP-01. Results: Erythematic-squamosal form was the most frequent recorded forms (73.7%) among the 9 clinical types. The expanded version of the pityriasis versicolor with typical localization of the affected areas made 80.9%, hyperpigmental form prevailed over hypopigmental form. Rare atypical forms of the disease (white spot type, erythrasmoid, urticarioid, lichenoid, ring-shaped, obliterated) were recorded in 11.8% of cases. 20.9% of patients had atypical localization of the pathological disease process on the face skin, axillary cavities, inframammary crease, inguinal fold, clunis, genitals, poples, dorslims of hands. In comparison with healthy persons which indicates perspiration and pH indicators 51.8 mA±0,46 and 5,33±0,004, patients with pityriasis versicolor had higher perspiration and pH in all tested areas and made the average of 60.1 мА±0,2 and 6,23±0,003 accordingly. Conclusion: Pityriasis versicolor is clinically polymorphyc. Along with the frequent forms, there are atypical forms with unusual localization of the disease process that may lead to diagnostic errors. Increased perspiration in torrid seasons causes to shift the skin pH in terms of alkaline content, and creates favorable environment for dissemination of Malassezia furfur.